Micrographia - Wilson, Emily, 1968- (University of Iowa Press, 2009)
Emily Wilson's eye travels the troubled boundaries between visible and invisible worlds, ranging from coastal Nova Scotia to the Andean highlands to Brooklyn's industrial Gowanus Canal to the poet's own backyard. Steeped in tradition but spoken in tones that are utterly distinctive, these intricate poems enter into the microscopic, micrographic spaces between words and things, between thinking and being.